Interrogative suspense in the Qur’anic discourse Rhetorical reading - Ahmed Muhammed Ameen, Muntaha; Mala Azeez, Salih (Zanco Journal of Human Sciences, 2023)
Arabic language is characterized for its diverse methods of expression its purposes each of these methods has its own it is known that Qur’anic text includes a set of rhetorical methods, and the interrogative method is one of those important expressive methods in the language of the holly Qur’an, as it is one of the eloquent methods performing different meanings through the context. The research sheds light on the figurative meaning emanating from the suspense to which the interrogation comes out, as this method leads to the suspense of the recipient to follow and understand the text and anticipate what will happen to the end of the event. And that is after alerting the recipient by the speaker to the content of the speech. It interrogates through rhetorical formation of the text to explain the reasons for its splendor and to highlight the beauty that emanates from the text.